Application of induced polarization gradient measurement in the exploration of the sanjiaotong gold mining area on the northern margin of the Qinghai Tibet Plateau - Zhou, Hao; Li, Shanping; Wang, Yadong; Lu, Yongzhuo; Zhang, Xinli; Feng, Jianping; Yuan, Yongtao (Frontiers in Earth Science, 2025)
With the increasingly difficult situation of mineral resources in various countries around the world, there is an urgent need for effective deep. Exploration techniques and methods to expand mineral resources and enhance the survival capacity of mines. The traditional artificial source electromagnetic method has limitations in exploration depth, accuracy, and other aspects. In contrast, the induced polarization ladder, as an effective electromagnetic (EM) exploration method, has the characteristics of high depth penetration, high accuracy, and strong adaptability. The Sanjiaodiang gold mine is located in the middle section of the Saishiteng Mountain on the northern edge of the Qaidam Basin in the northern part of the Qinghai Tibet Plateau. The mining area exhibits two main types of gold mineralization, namely, quartz vein type and alteration mylonite type, indicating multiple periods and stages of mineralization. The pyritic monzonitic granite and gabbro in the SB2 and SB4 alteration zones are characterized by high resistance and polarization, while ore-bearing geological bodies such as limonized granodiorite and strongly limonized gabbro display elevated polarization levels, potentially leading to abnormal polarization phenomena. Two induced polarization anomalies were defined based on apparent resistivity and apparent polarization characteristics. These anomalies primarily result from tectonic alteration zones. Following subsequent geochemical exploration and engineering verification, 12 tectonic alteration zones and over 40 gold mine (chemical) bodies have been delineated. Therefore, induced polarization intermediate gradient anomaly proves to be a promising prospecting method in gold mine exploration. The induced polarization gradient measurement method has played a good demonstration role in exploring quartz vein type and altered mylonite-type gold deposits worldwide. Induced polarization gradient has been widely used in the exploration of metal deposits in many countries due to its advantages and will play a more significant role in the search for hidden metal deposits.